Spatial patterns of ecosystem services and their determinants in small mountainous watersheds - LIU Rui; FAN Tianhu; WANG Keyu; XIAO He (Guan'gai paishui xuebao, 2024)
【Objective】 This paper is to address the research gap in ecosystem services of small mountainous watersheds and provide scientific support for comprehensive management and sustainable development of such regions. 【Method】 We take the Pengxi River Basin as an example. The InVEST model was used to evaluate water and soil conservation services in the region. The region was divided into different geomorphic types based on the terrain undulation and altitude. The geographical detector was then used to identify the dominant influencing factors and their interactions in different landform types. 【Result】 Spatially, water conservation increased from the north to the south, with its lowest value observed in the low-altitude areas (239.52 mm/m2) and the highest value observed in small undulating middle mountains (591.00 mm/m2). In contrast, soil retention increased from the south to the north, and increased with the elevation of landform gradients. Land use types and NDVI are the primary factors influencing water conservation and soil retention, respectively, with the forest and grassland performing particularly well. 【Conclusion】 In areas with high landforms gradients, ecological restoration needs to consider multiple factors to enhance water conservation and soil retention in the region.